2021
DOI: 10.1101/2021.09.03.21263103
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The prevalence of adaptive immunity to COVID-19 and reinfection after recovery – a comprehensive systematic review and meta-analysis

Abstract: Objectives This study aims to estimate the prevalence and longevity of detectable SARS-CoV-2 antibodies as well as T and B memory cells during infection with SARS-CoV-2 and after recovery. In addition, prevalence of COVID-19 reinfection, and the preventive efficacy of previous infection with SARS-CoV-2 were investigated. Methods and analyses A synthesis of existing research was conducted. The Cochrane Library for COVID-19 resources, the China Academic Journals Full Text Database, PubMed, and Scopus as well as… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 127 publications
(222 reference statements)
0
9
0
Order By: Relevance
“…A low risk of reinfection and a very low risk of severe or lethal COVID‐19 for those who recovered from a primary infection were reported in the vast majority of the published studies, as well in the available systematic reviews 108–111 . Most of the available information, however, included data preceding the emergence of the Omicron wave, 110 or relied upon very preliminary data 108 .…”
Section: Discussionmentioning
confidence: 99%
“…A low risk of reinfection and a very low risk of severe or lethal COVID‐19 for those who recovered from a primary infection were reported in the vast majority of the published studies, as well in the available systematic reviews 108–111 . Most of the available information, however, included data preceding the emergence of the Omicron wave, 110 or relied upon very preliminary data 108 .…”
Section: Discussionmentioning
confidence: 99%
“…This infection-blocking value was subjected to a sensitivity analysis. Vaccine protection is modelled in the context of naturally acquired immunity following SARS-CoV-2 infection, whereby natural immunity is assumed to reach peak immunity of 95% aligned with findings from Chivese and colleagues, 11 before waning exponentially to 20% in 600 days. 12…”
Section: Methodsmentioning
confidence: 99%
“…Other studies, albeit on smaller samples [27,28], have shown the presence of anti-SARS-CoV-2 S-RBD IgG at 14 months in recovered patients. More recently, an interesting meta-analysis included 54 studies from 18 countries for a total of 12,011,447 individuals with 8-month (average) post-infection follow-up [29]. Overall, the authors demonstrated in these subjects the presence of IgG, CD4+ T lymphocytes and B memory cells in 90.4%, and 80.6% of the cases respectively; moreover the prevalence of a reinfection was 0.2%.…”
Section: Duration and Type Of Immunity From Previous Sars-cov-2 Infec...mentioning
confidence: 99%